2021
DOI: 10.1016/j.ijid.2020.11.137
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and resistance of pathogens in infected patients within 1 year after heart transplantation

Abstract: Background: Infection is a major cause of morbidity and mortality after heart transplantation (HT). However, there have been few data on clinical manifestation, distribution, and resistance of pathogens in the infected population of heart transplant recipients. Methods: We conducted a single-center retrospective study on patients who underwent HT in Wuhan Union Hospital from August 3, 2012 to July 30, 2016. Risk factors for infections that occur within 1 year after HT were investigated by multivariable logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 26 publications
(34 reference statements)
0
6
0
Order By: Relevance
“…The prevention and control of MDROS is currently one of the biggest challenges in infection control. In recent years, the infection of MDROS in different countries and regions has been increasing [ 10 , 11 ]. Through χ 2 test statistics, it was found that, except for age and combined cardiovascular disease and MDROS infection in orthopedic trauma patients, there was no significant correlation, and the other factors were significantly correlated with MDROS infection in orthopedic trauma patients ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…The prevention and control of MDROS is currently one of the biggest challenges in infection control. In recent years, the infection of MDROS in different countries and regions has been increasing [ 10 , 11 ]. Through χ 2 test statistics, it was found that, except for age and combined cardiovascular disease and MDROS infection in orthopedic trauma patients, there was no significant correlation, and the other factors were significantly correlated with MDROS infection in orthopedic trauma patients ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, 31% of 82 patients with a bacterial infection within 1 year of a heart transplant had multidrug-resistant pathogens [22]. A further evaluation of 147 patients with heart transplants and infections with 259 pathogens found that there were 64 multidrug-resistant bacteria [23]. The low rates of antimicrobial resistance in the current study may be explained by some degree of underreporting of the diagnosis.…”
Section: Key Considerations Regarding the Findingsmentioning
confidence: 43%
“…This may be important as a prospective study of 138 patients who underwent cardiac surgery found that multidrug-resistant bacterial isolates were widespread and there are increasingly emerging strains of extended-spectrum beta-lactamases-producing Gram-negative bacteria Klebsiella pneumoniae, Pseudomonas aeruginosa, and Escherichia coli, especially, among patients with prolonged admission to intensive care units [20]. The studies of multidrug resistance have been evaluated in other types of patient cohorts [21][22][23]. In a study of patients with in-hospital cardiac arrest and nosocomial infection, 10 out of 35 patients (28%) had multidrugresistant pathogens [21].…”
Section: Key Considerations Regarding the Findingsmentioning
confidence: 99%
“…In a Brazilian case report, a 59 year old male heart transplant patient went into septic shock and multiple organ failure leading to death 50 days post transplantation due to infection with multidrug resistant Klebsiella pneumonia [63]. In China's Wuhan Hospital, of 299 heart transplant patients, 49.2% were found to be infected with 259 different pathogens [64]. Of these 147 infected patients, 64 multidrug resistant bacteria were detected within one year after the transplant.…”
Section: The Implications Of Multidrug Resistance For the Disruption ...mentioning
confidence: 99%